Contribuições a um pensar sociológico sobre a deficiência - Piccolo, Gustavo Martins (2012)
Throughout modern history the deficiency has been described mainly by the medical knowledge. In this paper we propose to investigate the importance of theory toward understanding the cited phenomenon on other bases than the accepted hegemonic, for this, we assumed that only a movement led by a revolutionary theory can effectively exercise the role of combatant lead. The development cited to materialize mainly through a process of dive on the writings of the London group called Disability Studies, representative current of a movement that can be seen as an inflection point on the historically dominant knowledge in dealing with disabilities, based on explanatory concepts from the field of sociology. Our work will be focused on this literature , aiming to compose a scenario which presents the historical development of this movement, as well as some of its limitations and possibilities to be explored. By materializing a theoretical search process, this work constitutes primarily as a literary composition (involving review, seizure, analysis, explanation and creation of literature), with the guidelines the historical materialism theory, though it does not materialize a Marxist work strict sense. Prior to submission of detailed theoretical corpus, we conducted a methodological process by state of the art on the dissertations and theses produced on (post-)graduate programs accredited by CAPES in fields related to sociological science (Sociology, Social Sciences, Anthropology and Political Science) between 1990 and 2010, mister universe by which Londoners develop their relations on disability. After collecting these data we found empirically that almost nothing was written about disability in the sociological fields. In 5691 texts of sociology cataloged only 10 (0.18%) dealt directly on disability. These data do not show significant changes when we compared the texts produced in the Graduate Program in Anthropology and Political Science. In anthropology, 1893 works were produced, and only 5 (0.26%) of these papers have disability as the main object of study, the same number found in Political Science in a universe of 1211 theses and dissertations. Of the 20 works found in a universe of 8798, only two made sporadic references to the London group. Thus, the deficiency still seems primarily as a medical phenomenon, a pre-sociological issue, not worthy of note to be represented as a matter of research in the sciences that make use of social analysis. In this sense, a question inevitably tends to be made: How to develop emancipatory policies for people with disabilities if the benchmark it leaves is inextricably linked to disability as a condition of dependency? Policies and practices need to be libertarian concepts and epistemologies also libertarian. But such concepts exist and seeking to appropriate the same we did a real scan magazine articles published in Disability & Society, the most important journal in the existing sociological analysis of disability. From June 1986 to July 2011 the magazine published 1487 articles, all in English, although produced by authors from more than 30 countries. Of these, 383 were read in full, which allowed us to compose the lines of this work, having as a foundational assumption the idea that disability is a product of social oppression inserted over the differences expressed by the body of his subjects, so, it is created by the intrinsic insensitivity of the environment in which we operate. From the literature review indicated themes were extracted to analyze the contributions and limits of social approach to disability and the urgent need ownership of their constructs. We conclude that the deficiency to be a category created shown capable of overcoming, whose objective conditions are given in the interstice of capitalist sociality, though never effected due to the structurally exclusive composition that features this system. Having all the means to overcome this oppressive condition that involves people with disabilities and does not exceed it is a phenomenon that highlights so nuclear forms the split between essence and existence, hence the need in fighting against these alienations, which reduces human beings the simple desire to have, the role of mere objects, thus, dispossessed or pruned sharply as the subjective capacity for self-determination, the choice of destination and the means of its attainment. The aforementioned struggle will succeed only when that full coincidence of changing circumstances and the transformation of consciousness, hallmark of any revolutionary act. Revolution, therefore, that never ceased to be the transformation of economic, political and cultural structures, linked by awareness the truths and prohibitions of the system that oppresses us. Only to discover their real interests can actually propose to overcome them. Precisely at the intersection of these elements, the thought of Marx's arises such as philosophy unsurpassed in our time because of its critical and emancipatory property; the dialectical unity between the study of capital and call for its overthrow, the analysis of alienation and fetishism by which we are involved and proposals for the disposal of all the conditions within which a man is to be reduced, abandoned, mutilated, despised. We need to bring Marxism to the analytical field of disability, that is our commitment and the universe with which the reader will encounter now.